Optimal trade policies under product differentiations - Yang, Yong-cong; Nie, Pu-yan (Journal of Business Economics and Management, 2020)
This article focuses on the optimal international trade policy considered product differentiations. A duopoly model with a home firm in a developing country and a foreign firm in a developed country is established. The findings indicate that, the optimal tariff relies on the product differentiations significantly. On one hand, higher marginal cost of home firms have opposite effects on optimal tariff compared to higher marginal cost of foreign firms. On the other hand, the optimal tariff is monotonically decreasing in the amount of consumers caring about brands and increasing in the scale of consumers not caring about brands. Moreover, an increase in the marginal cost and transportation cost of imported goods triggers price rising in domestic market as the market power of home firms is consolidated. In addition, a foreign firm may withdraw from domestic market if its competitive advantages vanishes under high tariffs.